1984
DOI: 10.1093/jac/14.5.463
|View full text |Cite
|
Sign up to set email alerts
|

An in-vitro system for determining the activity of compounds against the intracellular amastigote form of Leishmania donovani

Abstract: A method has been defined for infecting primary mouse peritoneal macrophages with amastigotes of Leishmania donovani in vitro, and analysing the response of the infected macrophages to treatment with drugs. The growth of intracellular amastigotes was inhibited by all clinically used antileishmanial drugs. Toxic effects on macrophages were observed with some drugs. Other experimental antileishmanial compounds were active in this system. This test is proposed as an initial screening test for the discovery of nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
126
0
2

Year Published

1987
1987
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(133 citation statements)
references
References 0 publications
5
126
0
2
Order By: Relevance
“…Leishmanicidal activity against intramacrophagic amas tigotes was performed on infected mouse peritoneal macrophages according to the method of Neal & Croft (1984).…”
Section: In Vitro Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Leishmanicidal activity against intramacrophagic amas tigotes was performed on infected mouse peritoneal macrophages according to the method of Neal & Croft (1984).…”
Section: In Vitro Evaluationmentioning
confidence: 99%
“…Mice were treated once a day for five consecutive days and sacrificed three days after the end of treatment. Drug activity was estimated by counting the number of amastigotes/500 liver cells in Giemsa stained impres sion smears prepared from the weighed livers of treated and untreated mice (Neal & Croft, 1984).…”
Section: In Vivo Evaluationmentioning
confidence: 99%
“…In view of the literature precedent [11,12] and our above results with T. b. rhodesiense we decided to screen our compound library against Leishmania donovani [21]. Using HU3 intracellular amastigotes at 30 mM only 8, 9, 12 and 20 showed any activity, with 39.7, 13.8, 11.6 and 2.7% inhibition respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies have shown that paromomycin can effectively kill both promastigotes and amastigotes (Neal and Croft 1984;Gebre-Hiwot et al 1992;Neal et al 1995). The 50% effective dose (ED 50 ) of paromomycin against L. donovani amastigotes ranges from 10 to 50 lM.…”
Section: Paromomycinmentioning
confidence: 99%